Valuation,measuring and managing the value of companies - Koller, Tim,Goedhart, Marc,Wessels, David
Valuation : measuring and managing the value of companies / Tim Koller, Marc Goedhart, David Wessels .- Hoboken, NJ : Wiley , 2015 .- xvii, 825 p. ; 26cm .- 9781118873700